ChemInform Abstract: Reversible Hydrogenation—Oxidative Dehydrogenation of Quinolines over a Highly Active Pt Nanowire Catalyst under Mild Conditions. Issue 1 (7th January 2014) - Ge, Danhua; Hu, Lei; Wang, Jiaqing; Li, Xingming; Qi, Fenqiang; Lu, Jianmei; Cao, Xuequin; Gu, Hongwei
Abstract The method avoids high temperatures and pressures and the catalyst can be recycled easily.